Chemoselective Electrochemical Oxidation of Secondary Alcohols Using a Recyclable Chloride-Based Mediator - Sommer, Florian; Kappe, C. Oliver; Cantillo, David (Synlett, 2021)
Selective anodic oxidation of alcohols in the presence of other functional groups can be accomplished by using nitroxyl radical mediators. However, the electrochemical chemoselective oxidation of secondary alcohols in the presence of primary alcohols is an unsolved issue. Herein, we report an electrochemical procedure for the selective oxidation of secondary alcohols by using an inexpensive chloride salt that acts as a redox mediator and supporting electrolyte. The method is based on the controlled anodic generation of active chlorine species, which selectively oxidize secondary alcohols to the corresponding ketones when primary hydroxy groups are present. The method has been demonstrated for a variety of substrates. The corresponding ketones were obtained in good to excellent yields. Moreover, the chloride salt can be easily recovered by a simple extraction procedure for reuse, rendering the method highly sustainable.
Keywords: electroorganic synthesis; alcohols; oxidation; redox mediators; anodic oxidation; sustainability